TEORI HUMANISTIK DAN KONSTRUKTIVISTIK DALAM PSIKOLOGI PENDIDIKAN KONTEMPORER - Adhela Falaby Rahman; Dwi Cahyo Setyono; Vava Iman Agus Faisal (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2025)
This article aims to examine the relevance of both theories within the context of modern education, which emphasizes holistic, active, and meaningful learner development. This study employs a literature review method by analyzing various academic sources, including books, national and international journals, and scholarly documents related to humanistic theory, constructivist theory, and contemporary educational psychology. The findings indicate that humanistic learning theory highlights the importance of affective aspects, learner autonomy, self-actualization, and positive relationships between teachers and learners. Meanwhile, constructivist theory positions learners as active agents who construct knowledge through experience, social interaction, and cultural contexts. In contemporary educational practice, these two theories are complementary and highly relevant to learner-centered learning, collaborative learning, and the development of 21st-century skills. Therefore, the integration of humanistic and constructivist learning theories contributes significantly to strengthening adaptive, humanistic, and contextual practices in educational psychology.